Analisis Ragam Hias dan Pemaknaannya pada Arsitektur Rumah Tradisional di Desa Lambunot, Aceh Besar - Zulhadi Sahputra; Mujibatur Rahmi (Fakultas Seni Rupa dan Desain ITB, 2023)
The Aceh Traditional House (Rumoh Aceh) is one of the cultural artifacts of Aceh, whose ornaments carry values and identity symbols that represent the Aceh architectural locality. This study aimed to describe the exploration of its decoration and its meaning. The exploration focuses on the settings, types, and basic shapes of the decorations used in the house. This ornamental variety shows every design element of the house’s façade, which used certain motifs. This research used a comparative study method with a case study approach for an object analysis conducted in an Acehnese traditional house in Lambunot Village. The analysis shows that the meaning of the decoration is dominated by floral motifs such as motif pucok rebong, on cirih, bungong seulanga, bungong awan-awan, bungong seuleupok, bungong tabue, bungong kipah, bulan bintang, bungong geulima, and tapak catoe. This study is expected to present the most convenient method for the Acehnese future generation in maintaining and interpreting the values of their traditional houses to perpetuate their architectural existence.